2015
DOI: 10.14814/phy2.12299
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of GLUT4 expression in smooth muscle prevents hypertension-induced changes in vascular reactivity

Abstract: Previous studies have shown that expression of GLUT4 is decreased in arterial smooth muscle of hypertensive rats and mice and that total body overexpression of GLUT4 in mice prevents enhanced arterial reactivity in hypertension. To demonstrate that the effect of GLUT4 overexpression on vascular responses is dependent on vascular smooth muscle GLUT4 rather than on some systemic effect we developed and tested smooth-muscle-specific GLUT4 transgenic mice (SMG4). When made hypertensive with angiotensin II, both wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Murine systolic blood pressure was measured by the IITC Life Science blood pressure (tail cuff) system (Woodland Hills, CA) as described previously (100). Hematocrit was measured by CritSpin® Micro-Hematocrit centrifuge with Digital Hematocrit Reader (StatSpin ® Company).…”
Section: Methodsmentioning
confidence: 99%
“…Murine systolic blood pressure was measured by the IITC Life Science blood pressure (tail cuff) system (Woodland Hills, CA) as described previously (100). Hematocrit was measured by CritSpin® Micro-Hematocrit centrifuge with Digital Hematocrit Reader (StatSpin ® Company).…”
Section: Methodsmentioning
confidence: 99%
“…The reduced expression of GLUT4 was observed in the aorta of hypertensive rats and mice (12,180). Moreover, the loss of GLUT4 expression in VSMCs results in abnormal vasoreactivity, whereas maintenance of GLUT4 expression prevents hypertension-induced alteration in vascular reactivity (13).…”
Section: Systemic Hypertensionmentioning
confidence: 96%
“…We found that the expression of GLUT varied based on blood vessel size, which is in accord with the variable densities of VSMCs in different size vessels ( Craggs et al, 2015 ). Another recent report indicates that GLUT4 may act as one of the regulators of the tonic capacity of VSMCs ( Atkins et al, 2015 ), suggesting that in CADASIL the blood flow restriction might be, in part, due to reduced GLUT4 (and GLUT2).…”
Section: Discussionmentioning
confidence: 99%